Analytical and simulation tools for the design of a flexible manufacturing system - Alfafara, Corinna Cutillar; Bohez, Erik L.J.; Tabucanon, Mario T.; Nagarur, Nagendra N.; Government of Belgium (Bangkok : Asian Institute of Technology, 1991)
Due to the diverse factors incorporated in each and every Flexible Manufacturing System, an appropriate and powerful tool is required to arrive at tailor made design concepts and analysis. Although CANQ, an analytical model, has been found to be robust in desigmng and analyzing FMSs, limitations in the design lead to inhibitions as to the accuracy of representation of the results to the desired and realistic FMS to be modeled. Simulation modeling not only overcomes these limitations, but also provides the modeler with a free hand in designing and analyzing the FMS. Through CANQ and Simulation, a proposed Flexible Manufacturing System has been studied. Conclusions from the analysis are twofold: that the proposed FMS to replace the existing manufacturing system is feasible by increasing productivity 7.7 % (CANQ result) and 20.53% (Simulation result); and that from among the factors varied in the simulation experiments: routings, dispatching rules, machine failures and part inspection, materials handling system; machine failures and part inspection caused the output rate to decrease by 36.31 %. The other factors have negligible effect on the production rate of the proposed design.
A thesis report submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Flexible manufacturing systems -- Simulation methods